CTIM-14. PELAREOREP AND GRANULOCYTE-MACROPHAGE COLONY-STIMULATING FACTOR (GM-CSF) WITH STANDARD CHEMORADIOTHERAPY/ADJUVANT TEMOZOLOMIDE FOR GLIOBLASTOMA MULTIFORME (GBM) PATIENTS: REOGLIO PHASE I TRIAL RESULTS. (9th November 2020) - Kendall, Jessica; Chalmers, Anthony; McBain, Catherine; Melcher, Alan; Samson, Adel; Phillip, Rachel; Brown, Sarah; Short, Susan
Abstract: BACKGROUND: Oncolytic viruses represent a novel treatment approach in GBM through oncolytic targeting as well as local immune activation. We designed a phase Ib, open-label study of intravenous reovirus (pelareorep) with GM-CSF alongside standard chemoradiotherapy to assess safety and tolerability. METHODS: 15 patients with newly diagnosed GBM were treated with GM-CSF 50mg subcutaneously (days 1–3) and pelareorep (days 4–5) in weeks 1 and 4 of chemoradiotherapy, and week 1 of adjuvant temozolomide course: 7 patients received 1x10 10 TCID50 (dose level 1); 8 received 3x10 10 TCID50 (dose level 2). The primary objective was to determine the maximum tolerated dose of pelareorep and GM-CSF with standard chemoradiotherapy. Secondary objectives were to gain preliminary assessment of the activity of the combination and assess treatment compliance. RESULTS: 1 dose limiting toxicity (DLT) and 20 SAEs were experienced overall; median number of SAEs per patient was 2. Commonest SAEs were nervous system disorders, predominantly seizures. SARs included fever/flu-like episodes (n=5), fall (n=1) and headache (n=1). Two SUSARs occurred in dose level 2, classed as vascular disorders manifesting as hypotension episodes – one was a DLT. Suspected relationship of SARs: pelareorep (n=6); temozolomide (n=1); radiotherapy (n=1); all study drugs (n=1). 87% of patients (n=13) completed chemoradiotherapy without unplanned delays. Adjuvant treatment was delayed in 21% of cycles overall, with the majority due to inadequate haematology/biochemistry values (44% of delays). Pelareorep was omitted in 4 instances in 4 patients during chemoradiotherapy and omitted in 4 instances in 3 patients during adjuvant treatment. CONCLUSION: We present the first clinical data using intravenous pelareorep with GM-CSF alongside standard chemoradiotherapy in patients with GBM, suggesting that the combination is tolerable. Further analysis is underway and efficacy results will be ready for presentation at the conference. This work was supported by CRUK, The Brain Tumour Charity, Yorkshire Cancer Research and Oncolytics Biotech Inc.